2023
DOI: 10.1111/anae.16009
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for chronic post‐surgical pain after lung and pleural surgery: a systematic review with meta‐analysis, meta‐regression and trial sequential analysis

Abstract: Chronic post-surgical pain is known to be a common complication of thoracic surgery and has been associated with a lower quality of life, increased healthcare utilisation, substantial direct and indirect costs, and increased long-term use of opioids. This systematic review with meta-analysis aimed to identify and summarise the evidence of all prognostic factors for chronic post-surgical pain after lung and pleural surgery. Electronic databases were searched for retrospective and prospective observational studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 108 publications
0
9
0
Order By: Relevance
“…It has been reported that the incidence of chronic pain at 3 and 6 months after thoracic surgery is 57% and 47% respectively, which is the highest among all types of surgeries. 9 Despite the introduction of video-assisted thoracic surgery, nearly 16% of patients still experience moderate to severe acute pain within 48 hours after surgery. 10 The optimal postoperative pain management strategy for VATS surgery remains uncertain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the incidence of chronic pain at 3 and 6 months after thoracic surgery is 57% and 47% respectively, which is the highest among all types of surgeries. 9 Despite the introduction of video-assisted thoracic surgery, nearly 16% of patients still experience moderate to severe acute pain within 48 hours after surgery. 10 The optimal postoperative pain management strategy for VATS surgery remains uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…We recruited patients scheduled to undergo thoracoscopic lobectomy between March 2023 and July 2023.The inclusion criteria were as follows: both genders, aged 18 to 65 years, BMI 18.5 to 28 kg/m2, ASA classification I to III. Exclusion criteria included: (1) patients with known allergies to the active ingredients of the drug being studied; (2) Patients at serious risk of increased intracranial pressure; (3) uncontrolled or untreated hypertension (resting systolic/diastolic blood pressure exceeding 180/100mmHg); (4) untreated or insufficiently treated hyperthyroidism; (5) patients requiring other surgeries during the study period or experiencing complications that would affect the study evaluation during or after surgery; (6) patients unwilling to participate after being informed about the study; (7) Post-operative planned admission to intensive care unit (ICU) for further treatment of patients; (8) patients with a history of severe psychiatric disorders or currently experiencing severe psychiatric disorders; (9) patients with congestive heart failure, a history of severe angina, or unstable angina or myocardial infarction within the past six months; (10) Prior to inclusion in the study, each patient will be tested on their ability to perform the Numeric Pain Scale Assessment (NRS), Patient Controlled Analgesia (PCA) pump operation, answer the telephone, and comprehend the Neuropathic Pain Syndrome Inventory (NPSI), and those who are unable to comprehend the relevant operations will be excluded from the study; (11)…”
Section: Study Design and Patient Enrollmentmentioning
confidence: 99%
“…Severe pain immediately after VATS can delay postoperative recovery by disrupting effective deep breathing and coughing ( 11 ). Furthermore, intense pain in acute postoperative period is strongly associated with chronic post thoracotomy pain syndrome, which impairs the quality of life ( 14 ). Therefore, various multimodal approaches have been introduced to reduce pain after VATS.…”
Section: Discussionmentioning
confidence: 99%
“…The severe postoperative pain experienced immediately in the PACU, combined with incomplete arousal from anesthesia, can lead to agitation and worsen postoperative recovery ( 26 ). Furthermore, the intensity of pain immediately after surgery in the PACU is correlated with the development of chronic pain ( 14 , 27 ). Therefore, even though there was no significant difference in pain up to 24 h after surgery between the two groups, we believe that reduction in immediate pain in the group N is noteworthy.…”
Section: Discussionmentioning
confidence: 99%
“…The three basic concepts of pharmacotherapy for postoperative pain are the use of various analgesic methods to minimize the use of opioid drugs and their side effects ( 30 ), “around-the-clock” administration of sufficient analgesic drugs at a fixed time ( 31 ), and administration of the drug in accordance with the package insert and with simultaneous monitoring of liver and kidney function. As mentioned above, it is very important to provide sufficient analgesia in the acute phase and to prevent the pain from becoming chronic ( 32 ). Among the many medications available, the key ones other than opioids are described below.…”
Section: Treatment Options For Reducing Ptpsmentioning
confidence: 99%